2021
DOI: 10.5114/jcb.2021.112115
|View full text |Cite
|
Sign up to set email alerts
|

Comparing multichannel cylinder and 3D-printed applicators for vaginal cuff brachytherapy with preliminary exploration of post-hysterectomy vaginal morphology

Abstract: Purpose: To compare dosimetric parameters of multichannel cylinder (MCC) and 3-dimensional (3D)-printed plans for high-dose-rate vaginal cuff brachytherapy (VBT) and to explore vaginal morphologies after hysterectomy.Material and methods: Forty-eight patients with gynecological cancer who required VBT after hysterectomy were investigated. To develop a 3D-printed applicator, computed tomography images were obtained with contrast-soaked vaginal gauzes placed in situ to mould vaginal anatomy. 3D digital model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…MCC applicators have become more popular because of their dose exibility [4]. However, the vagina may not be cylindrical because of surgery and anatomic irregularities [3]. Furthermore, MCC applicators are limited to various applications owing to air gaps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MCC applicators have become more popular because of their dose exibility [4]. However, the vagina may not be cylindrical because of surgery and anatomic irregularities [3]. Furthermore, MCC applicators are limited to various applications owing to air gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Personalized vaginal applicators are one choice to overcome the limitations of MCC applicators [12]. Yan et al showed that 3D-printed applicators obtained signi cant improvements in CTV-1 cm V100 (by 13%) and D90 (by 11%) when compared to MCC; 3D-printed applicators demonstrated superiority over MCC in terms of OARs protection [3]. In addition, the advantages of 3D-printing technology include versatility, costeffectiveness, and accuracy [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of POVBT techniques, a rich variety of applicators with different shapes (e.g., cylindrical, irregular, or spherical) and materials (polyphenylsulfone plastic, photopolymer, acrylic, or salinefilled) [9][10][11][12] have emerged. The diversity of applicators makes it difficult to create an automatic segmentation model of POVBT.…”
Section: Discussionmentioning
confidence: 99%